Predicted Studies of Branched and Cross-Linked Polyurethanes Based on Polyhydroxybutyrate with Polycaprolactone Triol in Soft Segments - Brzeska, Joanna (Polymers (Basel), 2020)
The number of cross-links in the non-linear polyurethane structure is the basic factor affecting its properties. Selected properties of aliphatic polyurethanes with soft segments made of different amounts of polycaprolactonetriol, polycaprolactonediol and synthetic, telechelic poly([R,S]-3-hydroxybutyrate) were determined. On the basis of changes in polyurethane properties, the correlation between these properties and the construction of soft segments was found. The structure of polyurethanes, their morphology, hydrophilicity, thermal and mechanical properties were examined. These properties were changed linearly up to 15% content of polycaprolactonetriol in soft segments. A further increase in the amount of triol causes that these properties are mainly determined by the high number of cross-links.